2008
DOI: 10.1093/chemse/bjn078
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of SC45647 and Sucralose by Rats Selectively Bred for High and Low Saccharin Intake

Abstract: Mammals' affinity for sweet tastes exists alongside dramatic variation among species and individuals in responses to sweeteners. The present paper focused on consumption by Occidental High- (HiS) and Low-Saccharin (LoS)-consuming rats in 23-h 2-bottle tests of 2 sweeteners for which few data from rats are available: SC45647 and sucralose. Every HiS and LoS rat preferred SC45647 to water at every concentration, with HiS rats consuming it more avidly. Most HiS rats preferred sucralose to water at one or more con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…Subsequently, these rats were also found to differ in ethanol intake (HiS > LoS), thus providing a finding complementary to the results described above based on rats bred for differences in ethanol intake [18]. General differences in size or ingestive behavior do not apparently account for differences in saccharin or ethanol intake, as the two lines do not consistently differ in body weight or food or water intake [17, 19, 20]. Furthermore, in HiS and LoS rats, body weight was not correlated with food intake, wheel running, or meal patterning [20], and sucrose preference and avidity did not significantly covary with body weight [17].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Subsequently, these rats were also found to differ in ethanol intake (HiS > LoS), thus providing a finding complementary to the results described above based on rats bred for differences in ethanol intake [18]. General differences in size or ingestive behavior do not apparently account for differences in saccharin or ethanol intake, as the two lines do not consistently differ in body weight or food or water intake [17, 19, 20]. Furthermore, in HiS and LoS rats, body weight was not correlated with food intake, wheel running, or meal patterning [20], and sucrose preference and avidity did not significantly covary with body weight [17].…”
Section: Introductionmentioning
confidence: 67%
“…In addition to differences in saccharin intake (the basis of selective breeding), the two lines have also been shown to differ in a similar direction in the preference, intake or avidity of sucrose, Polycose and sodium chloride solutions, as well as other non-caloric sweeteners [19, 22]; they do not appear to differ in their aversion or avidity for sour (quinine and sucrose octaacetate) or bitter (citric acid) tastes [22]. To determine whether HiS and LoS rats differ in sweet intake when a response requirement was imposed, they were tested for operant responding for sucrose pellets under fixed- and progressive-ratio (PR) schedules of reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Both male and female rats prefer sweet solutions to water [19;20]; however, female rats have been shown to display stronger preferences for both nutritive and non-nutritive sweet solutions than male rats [21]. Furthermore, female but not male rodents were shown to use sugary treats as a “comfort food” during periods of experimentally-induced stress [22].…”
Section: Introductionmentioning
confidence: 99%
“…Our lab and others have demonstrated that rats display considerable variation in their acceptance of sucralose [12, 14, 32, 33], and that these differences are taste-driven [19]. However, the degree to which SP and SA differ in their perception of bitter- and sweet-like taste qualities remains unclear, as do the potential consequences of this differential perception of taste on caloric intake and diet choice.…”
Section: Discussionmentioning
confidence: 99%